An Experiential Learning Approach to Primary Palliative Care Nursing Education: The Comfort Shawl Project. Issue 6 (December 2017) - Glover, Toni L.; Horgas, Ann L.; Castleman, Joan; Turpening, Paula; Kittelson, Sheri
Abstract : The need for palliative care is growing along with a rapidly aging population. To meet this need, the American Association of Colleges of Nursing developed palliative care competencies that all nurses should achieve before graduation. Many of these competencies rely on direct experience in caring for patients facing serious illness, leading to an increased emphasis on experiential learning in nursing curricula. Experiential learning is the process of creating knowledge through transformative experiences outside the traditional classroom setting. The Comfort Shawl Project is a service learning project that provides senior nursing students with a yearlong immersion in palliative care. Experiential learning activities include attending the interdisciplinary palliative care team meeting, gifting handcrafted shawls to patients, writing reflections, participating in extracurricular events, and sharing the impact of the project through written papers and presentations. The project has been successful in helping nursing students achieve palliative care competencies, including communicating effectively and compassionately with patients and families and recognizing one's own beliefs about serious illness and death. This project addresses the need to achieve primary palliative care competencies for nursing students. Clinical experiences in palliative care are vital to supplementing didactic learning, and this project could be replicated in a variety of academic settings.